An Overview of Construction Market of Sri Lanka - Sandeepan Saha; Dipak Paul (International Journal of Rural and Regional Development, 2023)
This paper provides an overview of the construction market in Sri Lanka, with a focus on the Colombo region. It discusses the strengths, weaknesses, opportunities, and constraints of the construction market in the country. The main drivers of the construction sector are identified, including urbanization and infrastructure development. The paper explores the ease of embarking on international construction projects within the Colombo region, noting that while the Sri Lankan government encourages foreign investment, the local construction industry may not always welcome foreign companies. China and India are recognized as key players in the Sri Lankan construction sector. The ease of embarking on international construction projects within the Colombo region is explored. It is noted that while the Sri Lankan government allows foreign investment in infrastructure projects, the local construction industry is not always receptive to foreign construction companies. China and India are identified as key players in the Sri Lankan construction sector, with China playing a major role in funding and building major projects in the country. The main drivers of the construction sector are highlighted, such as urbanization and the government's plans for the development of new cities. The importance of infrastructure development and improving energy supply is emphasized as key drivers for economic growth. The paper also highlights the key operational and commercial challenges faced by companies seeking to undertake international construction projects in the region, including political and legal issues, cultural differences, technical limitations, managerial challenges, economic constraints, environmental concerns, social factors, and corruption. The conclusion emphasizes the need for project managers to understand the local environment, remain flexible, and address the challenges associated with international construction projects in Sri Lanka. It also underscores the importance of foreign investment in the construction sector for the region's economic development
Keywords: Sri Lanka; construction industry; construction materials; regional corporation; skilled labor